Evolution and Development - Evolution and Development (Wiley, 2026)
Evolution and Development is an interdisciplinary journal at the interface of evolutionary and developmental biology. The journal welcomes papers from evo-devo biologists, covering approaches including paleontology, population biology, molecular evolution, and genetics. We also accept relevant submissions from professionals in other fields, from theoretical biology to ecology to the history and philosophy of science.
FI 0.68
Q2
Keywords: Life Sciences; Evolution; Evolución; Acuerdos transformativos; Transformative agreements; Paleontología; Biología de poblaciones; Genética molecular